EFFECT OF PHYSICAL EXERCISE AND YOGA ON BLOOD PRESSURE AMONG SCHOOL CHILDREN - P, Premalatha; C, Kanniammal; G, Valli; Mahendra, Jaydeep (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The principal aim of the study is to identify the effect of physical exercise and yoga on blood pressure (BP) among children, a common cardiovascular risk factor among children in recent years. Methods: A true experimental design was adopted to find the effect of physical exercise and yoga on selected children with increased BP and weight. The weight was inferred based on the World Health Organization (WHO) chart on body mass index for age. BP and height were measured and interpreted using the WHO height percentile chart for boys/girls and BP references of National Heart, Lung, and Blood Institute, to identify hypertensive children. Hypertensive children were given physical exercise and yoga, 5 days a week, for 6 months and control group led a normal lives. Results: In the pretest, 100% of the study and control group were prehypertensive. After 3 months of physical exercise and yoga, 21% of study group became normotensive which was significant at p=0.000 and it increased to 93% after 6 months with the significance of p=0.000. The weight and systolic BP (SBP) had a significant positive correlation. The age (p=0.001), number of family members, type of family (p=0.01), mother's occupation, family history of obesity, and chronic illness among fathers (p=0.05) had a significant association with SBP of the children. Conclusion: The study concluded that physical exercise and yoga reduced childhood hypertension as well as is a cost effective and easily practicable intervention for children to minimize cardiovascular risk during their adulthood.